Enrichment of tasks in initial formation of the Bachelor's Degree in Primary Education to attend deepening courses - Rafael Ramírez Uclés (Universidad de La Rioja, 2021)
Recent curricular regulations highlight the need to attend to high abilities, particularly students with mathematical talent. This proposal shows a training task example for future teachers to design enrichment tasks in an enhancement program. This work is based on didactic analysis as a teaching planning tool. Based on the characterization of mathematical talent and the notion of rich activities, some guidelines are established for the Primary Grade student analyze and design tasks for specially motivated or mathematical talented students in Primary Grade.